Analisis Pengaruh Citra Merek Terhadap Minat Berkunjung Ke Namu Coffee Duta Mas, Jelambar - Jonathan Yofan Tjandra; Dewanta Facrureza (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This research investigates the influence of brand image on interest in visiting Namu Coffee Duta Mas, Jelambar, Namu Coffee is a coffee shop / café located on Jl. Wijaya Kusuma No.13 RT09/RW09, Grogol Pertamburan, West Jakarta. Café is a place to relax and chat where visitors can order drinks and food.This research uses a descriptive quantitative method, by collecting data using Google Form / questionnaire with a total of 100 respondents calculated using the Slovin formula.The test results from this research produce valid, reliable and normal test data, and the hypothesis test results from this research show that dimensions 1 and 2 of brand image have no partial influence, but dimension 3 of brand image has a partial influence on the variables of interest. visit, and the results of this research test show that there is a simultaneous influence on the variableinterest in visiting at Namu Coffee Duta Mas, Jelambar.